Rhythmic Memory Consolidation in the Hippocampus - Nokia, Miriam S.; Penttonen, Markku (Frontiers in Neural Circuits, 2022)
Functions of the brain and body are oscillatory in nature and organize according to a logarithmic scale. Brain oscillations and bodily functions such as respiration and heartbeat appear nested within each other and couple together either based on phase or based on phase and amplitude. This facilitates communication in wide-spread neuronal networks and probably also between the body and the brain. It is a widely accepted view, that nested electrophysiological brain oscillations involving the neocortex, thalamus and the hippocampus form the basis of memory consolidation. This applies especially to declarative memories, that is, memories of life events, for example. Here, we present our view of hippocampal contribution to the process of memory consolidation based on the general ideas stated above and on some recent findings on the topic by us and by other research groups. We propose that in addition to the interplay between neocortical slow oscillations, spindles and hippocampal sharp-wave ripples during sleep, there are also additional mechanisms available in the hippocampus to control memory consolidation: A rather non-oscillatory hippocampal electrophysiological phenomenon called the dentate spike might provide a means to not only consolidate but to also modify the neural representation of declarative memories. Further, we suggest that memory consolidation in the hippocampus might be in part paced by breathing. These considerations might open new possibilities for regulating memory consolidation in rest and sleep.